Perceptions and attitudes towards the hospitality professions in Cyprus - Kyprianou, George; Zopiatis, Anastasios (My University, 2006)
The future of the hospitality industry depends on the quality of its people. The purpose of this research activity was to investigate the attitudes of secondary school students towards the hospitality professions. In addition, the study examines students’ perceptions towards the hospitality industry of Cyprus so as to identify whether the industry’s poor reputation is shared by young individuals ready to make their career decisions. Reflecting on the research findings, a suggestive profile of the secondary school student most likely to pursue a career in the hospitality industry is developed. Finally, the authors recommend specific actions that hospitality stakeholders could initiate in order to improve the perceptions and attitudes towards the professions of their industry.
Keywords: Cyprus Hospitality Industry; Hospitality education; Hospitality professions; Perceptions and attitudes of secondary school students